2014
DOI: 10.1177/0731684414567014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of framework structure and coupling modification on the properties of mesoporous silica/poly(methyl methacrylate) composites

Abstract: Mesoporous silicas (MPSs) with two-dimensional (2D) hexagonal framework (SBA-15) and worm-hole framework (MSU-J) were synthesized with poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) (P123) and a,o-polyoxypropylene diamine (D2000) as templates, respectively. Both SBA-15 and MSU-J were further modified with g-(methacryloyloxy) propyl trimethoxy silane (MAPTS) via post-grafting to prepare organic mesoporous silicas (denoted SBA-15-G and MSU-J-G, respectively) with -C ¼ C groups on the surface of mesopore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As can be seen, the incorporation of KIT‐6 nanoparticles into the 75/25 PVDF/PCL blend makes the interface of PVDF and PCL sharper, and this variation becomes more pronounced as the content of KIT‐6 increases. Rougher fracture surfaces of nanocomposites compared to the 75/25 PVDF/PCL blend, which is more evident in the 75/25/3 PVDF/PCL/KIT‐6 and 75/25/5 PVDF/PCL/KIT‐6 nanocomposites, could be attributed to the interface action between the filler and the polymer matrix; 41 as more crack deflections and smaller fracture areas are visible in SEM images of nanocomposites, it appears that KIT‐6 particles can act as a compatibilizer and enhance interfacial adhesion between components.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As can be seen, the incorporation of KIT‐6 nanoparticles into the 75/25 PVDF/PCL blend makes the interface of PVDF and PCL sharper, and this variation becomes more pronounced as the content of KIT‐6 increases. Rougher fracture surfaces of nanocomposites compared to the 75/25 PVDF/PCL blend, which is more evident in the 75/25/3 PVDF/PCL/KIT‐6 and 75/25/5 PVDF/PCL/KIT‐6 nanocomposites, could be attributed to the interface action between the filler and the polymer matrix; 41 as more crack deflections and smaller fracture areas are visible in SEM images of nanocomposites, it appears that KIT‐6 particles can act as a compatibilizer and enhance interfacial adhesion between components.…”
Section: Resultsmentioning
confidence: 97%
“…In terms of piezoelectric PVDF, according to the literature, 35 the addition of PCL could enhance the β‐phase content of PVDF, while to the best of our knowledge, up till now, no studies have been conducted on the effect of mesoporous silica particles on the piezoelectric properties of PVDF. It was shown that the physical properties of polymers, such as thermal and mechanical properties are affected by the addition of mesoporous silica particles; some researchers have reported that mesoporous silica particles can change the glass transition temperature ( T g ) of a polymer matrix and enhance its dynamic mechanical properties 32,33,36–40 as well as thermal stability 29,34,36–44 . Very little research has been reported on the influence of mesoporous silica on the miscibility of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. As shown in Figure 4, all the nanocomposites exhibit higher temperatures at T max compared with pristine epoxy suggesting that the decomposition is delayed due to the existence of polymer both inside and outside of the channel of silica aerogel [52]. These results suggest that the incorporated silica aerogels into epoxy matrix have an interpenetrating organic-inorganic network (IOIN) where the silica aerogel pores can be considered to be an inorganic network and the epoxy polymers could be introduced into these nanopores.…”
Section: Dynamic Mechanical and Thermal Propertiesmentioning
confidence: 92%
“…In another study of the same group, Jiao and co-workers studied the effect of chemical treatment and framework structure on the fracture behavior of PMMA/mesoporous silica nanocomposite. 66 It was found that, regardless to the framework structure, surface-treated mesoporous particles produced smaller aggregates than did those derived from untreated mesoporous particles. From the SEM photography, the fracture surface of untreated mesoporous particles/ PMMA composites was rougher than the fracture surfaces of the composite with silane treatment particles ( Figure 10).…”
Section: Mechanical Propertiesmentioning
confidence: 96%